Evaluating Emergency Preparedness And Health System Resilience: A Cross-Country Analysis Of COVID-19 Responses In OECD And LMIC Contexts - Muh Ibnu Sholeh; Himad Ali (International Journal of Health Systems and Policy, 2025)
The COVID-19 pandemic provided an unprecedented stress test for health systems and governance structures across both high-income (OECD) and low- and middle-income countries (LMICs). This study aims to evaluate how countries with differing economic capacities responded to the pandemic by analyzing three key dimensions: health system capacity, governance and emergency response, and recovery and adaptation policies. Using a mixed-methods comparative approach, we examined data from WHO, OECD, World Bank, and the COVID-19 Health System Response Monitor, supplemented by in-depth case studies of selected countries including Germany, South Korea, Indonesia, and Nigeria. Findings reveal that while OECD countries generally had higher baseline capacities such as hospital bed density and workforce ratios outcomes varied significantly due to differences in policy timing, public trust, and crisis coordination. Some LMICs, despite limited infrastructure, mobilized resources effectively through strong community engagement and past epidemic experience, notably in Vietnam and Rwanda. Governance quality, transparency, and prior exposure to health emergencies emerged as more critical to resilience than economic status alone. The study concludes that health system resilience is a multidimensional construct shaped by institutional adaptability, citizen compliance, and leadership capacity. These insights underscore the importance of integrating equity, trust-building, and cross-sector coordination into future global health preparedness strategies.